Selective recognition of Triamterene in biological samples by molecularly imprinted monolithic column with a pseudo template employed - Zhao, Xiao-Yun; Zhang, Hong-Wu; Liang, Zhen-Jie; Shu, Ya-Ping; Liang, Yong (Journal of separation science, 2013)
Melamine (MAM) was employed as a pseudo template to prepare a molecularly imprinted polymer monolithic column which presents the ability of selective recognition to Triamterene (TAT), whose structure was similar to that of MAM. Methacrylic acid and ethylene glycol dimethacrylate were applied as functional monomer and cross‐linker, respectively, during the in situ polymerization process. Chromatographic behaviors were evaluated, the results indicated that the molecularly imprinted polymer monolithic column possessed excellent affinity and selectivity for TAT, and the imprinting factor was high up to 3.99 when 7:3 of ACN/water v/v was used as mobile phase. In addition, the dissociation constant and the binding sites were also determined by frontal chromatography as 134.31 μmol/L and 132.28 μmol/g, respectively, which demonstrated that the obtained molecularly imprinted polymer monolith had a high binding capacity and strong affinity ability to TAT. Furthermore, biological samples could be directly injected into the column and TAT was enriched with the optimized mobile phase. These assays gave recovery values higher than 91.60% with RSD values that were always less than 3.5%. The molecularly imprinted monolithic column greatly simplified experiment procedure and can be applied to preconcentration, purification, and analysis of TAT in biological samples.